DOP36 Vedolizumab-treated IBD patients show an increased gut microbial diversity associated with a specific serum metabolic signature. (30th January 2023) - Pisani, L F; Crespi, G; Mellai, M; Flavio, C; Annunziata, M L; Manfredi, M; Luca, P; Porta, C
Abstract: Background: A role for gut microbes in IBD has been suspected since the early descriptions of potential infectious agents. IBD is clearly associated with intestinal dysbiosis, that is the imbalance in structures and functions of gut microbiota that disrupts host-microbe and immune homeostasis. Members of the commensal gut microbiota may play a role in etiopathogenesis of IBD. New therapies with diverse mechanisms of action inhibiting leukocyte trafficking or blocking inflammatory cytokines have revolutionized therapeutic approach. A less diverse microbiome, greater abundance of pro-inflammatory and depletion of species with protective mechanisms, such as short-chain fatty acid production, is associated with intestinal inflammation in IBD. Given that intestinal dysbiosis is a hallmark of IBD patients, we investigate the potential role of biologic drugs on both gut microbial and serum metabolomic in the restoration of microbial homeostasis. Methods: In 2020-2021, 238 IBD patients (CD=145, UC=93) and 45 healthy controls of the North Italy were enrolled. To define the characteristics of metabolic profile of IBD patients, three different machine learning models based on serum metabolic signatures were developed and applied for the random forest analysis of anti-TNF or anti-integrin users. Stool sample from anti-integrin (N=18) or anti-TNF (N=19)-treated IBD patients was profiled by 16S rRNA gene sequencing, to identify putative associations between medication and microbial composition. Results: In IBD patients untargeted metabolomics on serum samples confirmed that both most of the IBD patients (70% of anti-TNF and 100% of vedolizumab users) harbor a metabolic profile enriched of anti-inflammatory and antioxidant molecules. Noteworthy, vedolizumab-treated patients showed a higher microbial diversity than anti-TNF users along with an enrichment of both Bacteroidetes and Proteobacteria. Despite the prevalence of Firmicutes species (60, 85-62, 97%) in IBD patients, the Firmicutes/Bacteroidetes ratio of vedolizumab (2, 9:1) is lower than anti-TNF (5, 7:1) users, suggesting that anti-integrin-treated patients have an improved microbial composition. Conclusion: The gut microbiome is a key determinant of initiation and propagation of luminal inflammation in IBD. We describe the microbial composition and structure from a large cohort of IBD patients with different biologic therapies, and their metabolomic profile. We found a correlation between an improvement of dysbiosis and a more anti-oxidant and anti-inflammatory metabolic profile in vedolizumab-treated patients. Further experimental studies are important to mechanistically determine how biologic drugs differentially influence gut microbiota and metabolomic and how this may impact IBD course.